Modelling, simulating and parameter designing for traction power system with bidirectional converter devices - Jian Zhang (Wiley, 2022)
Abstract The bidirectional converter device (BCD) can substitute the substation rectifier and the energy feedback system (EFS) by transforming energy between the AC side and DC side. However, the performance of the railway system with BCDs as only converters has not been fully understood. A simulation approach is required to evaluate the system performance and guide the design. In this paper, the traction power supply system considering the capacity constraint of BCDs is modelled first, and the AC/DC power calculating algorithm is studied. A three‐layer double‐loop parameter designing strategy based on the enhanced brute force is proposed, which considers the N −1 principle. In the case study, the power source model for trains and power constraint for BCDs are verified. The boundary configuration set is obtained. The capacity of BCDs is at least 7 MW, while the slope is 0 and the no‐load voltage is between 1730 and 1750 V. Finally, compared with the system with rectifiers and EFSs, the system with BCDs has better performance, which is 46.7 V less of the rail potential, 127.8 V less of network voltage fluctuation, and 735.56 kWh per hour more of the feedback energy.